1989
DOI: 10.1152/jappl.1989.66.5.2032
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of vagal pulmonary C-fibers by a single breath of cigarette smoke in dogs

Abstract: Inhalation of cigarette smoke into the lower airway via a tracheostomy evokes immediate apnea, bradycardia, and systemic hypotension in dogs. These responses can still be evoked when conduction in myelinated vagal fibers is blocked preferentially by cooling but are abolished by vagotomy, suggesting that they are mediated by afferent vagal C-fibers. To examine this possibility, we recorded impulses in pulmonary C-fibers in anesthetized, open-chest dogs and delivered 120 ml cigarette smoke to the lungs in a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 0 publications
5
69
0
1
Order By: Relevance
“…Taken together, nicotine contained in the cigarette smoke exerts a direct stimulatory effect on both C-fiber afferents and RARs in the lungs (13)(14)(15)(16); the effect is more pronounced and consistent on the former. The electrophysiologic evidence further suggests the presence of acetylcholine nicotinic receptors on the membrane of sensory terminals of these lung afferents (13,16). The finding that nicotine is responsible for the smoke-evoked irritant effects on airway afferents was later confirmed in a study on healthy human volunteers when the intensity and detection of the airway irritation were measured using a psychophysical technique (7).…”
Section: Airway Afferents Involved In the Reflex Responses To Inhaledmentioning
confidence: 82%
See 2 more Smart Citations
“…Taken together, nicotine contained in the cigarette smoke exerts a direct stimulatory effect on both C-fiber afferents and RARs in the lungs (13)(14)(15)(16); the effect is more pronounced and consistent on the former. The electrophysiologic evidence further suggests the presence of acetylcholine nicotinic receptors on the membrane of sensory terminals of these lung afferents (13,16). The finding that nicotine is responsible for the smoke-evoked irritant effects on airway afferents was later confirmed in a study on healthy human volunteers when the intensity and detection of the airway irritation were measured using a psychophysical technique (7).…”
Section: Airway Afferents Involved In the Reflex Responses To Inhaledmentioning
confidence: 82%
“…The delayed response developed 10-20 sec after the smoke inhalation and was caused by nicotine-induced bronchoconstriction, mediated through the cholinergic reflex (16). Taken together, nicotine contained in the cigarette smoke exerts a direct stimulatory effect on both C-fiber afferents and RARs in the lungs (13)(14)(15)(16); the effect is more pronounced and consistent on the former. The electrophysiologic evidence further suggests the presence of acetylcholine nicotinic receptors on the membrane of sensory terminals of these lung afferents (13,16).…”
Section: Airway Afferents Involved In the Reflex Responses To Inhaledmentioning
confidence: 92%
See 1 more Smart Citation
“…Several studies have demonstrated that SP is a proinflammatory agent that influences various signaling transduction pathways within a complex inflammatory network by C-fiber afferent stimulation following external stimulation (1,4,9,14,22). In vivo studies have demonstrated the efficacy of antioxidants and free radical scavengers in ameliorating increases in endogenous SP levels (which may result in increased microvascular permeability via upregulated ICAM-1 expression, edema, and severe hypoxia) (11).…”
Section: Discussionmentioning
confidence: 99%
“…Afferent activity arising from the lung vagal sensory receptors was recorded by using techniques described elsewhere (24). Briefly, the left vagus nerve was left intact, whereas the right vagus nerve was sectioned.…”
Section: Methodsmentioning
confidence: 99%